2012
DOI: 10.1093/infdis/jis367
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and Breadth of the Neutralizing Antibody Response in the RV144 and Vax003 HIV-1 Vaccine Efficacy Trials

Abstract: Background. A recombinant canarypox vector expressing human immunodeficiency virus type 1 (HIV-1) Gag, Pro, and membrane-linked gp120 (vCP1521), combined with a bivalent gp120 protein boost (AIDSVAX B/E), provided modest protection against HIV-1 infection in a community-based population in Thailand (RV144 trial). No protection was observed in Thai injection drug users who received AIDSVAX B/E alone (Vax003 trial). We compared the neutralizing antibody response in these 2 trials.Methods. Neutralization was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
306
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(322 citation statements)
references
References 47 publications
13
306
1
2
Order By: Relevance
“…Moreover, the NAbs measured here in vaccinated macaques are higher than nAb responses in immune sera from human clinical trials using Env immunogens. In the Vax003 trial, neutralization of Tier 2 viruses using the A3R5 assay was infrequent and weak and no Tier 2 neutralization with this assay was seen in the RV144 trial (52).…”
Section: Neutralization Breadth Is Induced Against Heterologous Tier mentioning
confidence: 98%
“…Moreover, the NAbs measured here in vaccinated macaques are higher than nAb responses in immune sera from human clinical trials using Env immunogens. In the Vax003 trial, neutralization of Tier 2 viruses using the A3R5 assay was infrequent and weak and no Tier 2 neutralization with this assay was seen in the RV144 trial (52).…”
Section: Neutralization Breadth Is Induced Against Heterologous Tier mentioning
confidence: 98%
“…First, the ability of the passively transferred b12 broadly neutralizing antibody to protect macaques from simian/HIV (SHIV) infection is reduced if the constant region (Fc) of the antibody is modified in a manner that abrogates binding to Fc receptors on cells of the innate immune system [1]. Secondly, the recent RV144 vaccine trial in Thailand provided a modest level of protection from HIV infection, despite not inducing robust cytotoxic T lymphocyte (CTL) responses or broadly neutralizing antibodies [2,3]. A correlate of protection analysis of this trial revealed that the presence of antibodies capable of mediating antibody-dependent cellular cytotoxicity (ADCC) corresponded with protection when vaccinated individuals also had low levels of immunoglobulin (Ig)A antibodies that could inhibit IgG binding and induction of ADCC [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This was most clearly seen in the ALVAC/AIDSVAX RV144 HIV-1 vaccine efficacy trial, in which Env immunogens 92TH023 and A244 CRFAE_01 gp120s both expressed a dominant linear V2 epitope and bound with high-nanomolar affinity to the glycandependent V1V2 BnAbs PG9 and CH01 (16). Although both linear and glycan-dependent V2 epitopes were expressed on the A244 immunogen, the dominant V2 plasma antibody responses in this trial were targeted to linear V2 epitopes and not to the glycan-dependent BnAb epitope (14)(15)(16). A series of mAbs, the prototype of which is the mAb CH58, has been isolated from RV144 vaccines and shown to bind to linear V2 epitopes that include lysine 169 (16).…”
mentioning
confidence: 71%
“…Immunization of humans with Env proteins has not resulted in high plasma titers of BnAbs (14,15). Rather, dominant strainspecific neutralizing epitopes have selectively been induced.…”
mentioning
confidence: 99%